2022
DOI: 10.3390/cells11121933
|View full text |Cite
|
Sign up to set email alerts
|

Using Extracellular Vesicles Released by GDNF-Transfected Macrophages for Therapy of Parkinson Disease

Abstract: Extracellular vesicles (EVs) are cell-derived nanoparticles that facilitate transport of proteins, lipids, and genetic material, playing important roles in intracellular communication. They have remarkable potential as non-toxic and non-immunogenic nanocarriers for drug delivery to unreachable organs and tissues, in particular, the central nervous system (CNS). Herein, we developed a novel platform based on macrophage-derived EVs to treat Parkinson disease (PD). Specifically, we evaluated the therapeutic poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…This intervention enhanced neuronal survival and behavioral traits. Along with that it reduced neuroinflammation . In a 6-OHDA rodent model of PD, GDNF injection presented neuroprotection and regeneration of DA neurons .…”
Section: Novel Targets For Improved Pd Therapeuticsmentioning
confidence: 80%
See 1 more Smart Citation
“…This intervention enhanced neuronal survival and behavioral traits. Along with that it reduced neuroinflammation . In a 6-OHDA rodent model of PD, GDNF injection presented neuroprotection and regeneration of DA neurons .…”
Section: Novel Targets For Improved Pd Therapeuticsmentioning
confidence: 80%
“…Along with that it reduced neuroinflammation. 148 In a 6-OHDA rodent model of PD, GDNF injection presented neuroprotection and regeneration of DA neurons. 149 GDNF is inherently less stable, and hence therapeutic intervention is challenging.…”
Section: Glial Cell-line Derived Neurotrophic Factor (Gdnf)mentioning
confidence: 99%
“…GDNF is known to increase neuronal survival. GDNF-enriched EVs treated with transgenic Parkin Q311 (X) Intranasal injection of a mouse enhanced neuronal survival, decreased neuroinflammation, and improved motor performance in the Parkinson’s disease animal model [ 261 ].…”
Section: Applications Of Evs As Nanotheranostic Targets In Cnsmentioning
confidence: 99%
“…As expected, it was found that EVs collected from the conditioned media of GDNF-transfected macrophages contained GDNF proteins as well as genetic material-GDNF-encoding DNA. Moreover, applying GDNF-EVs via intranasal administration to the mouse model of Parkinson disease (transgenic Parkin Q311(X)A mice) led to a significant improvement in mobility, an increase in neuronal survival, and a decrease in neuroinflammation in mice [73].…”
Section: Genetic Engineering Of Donor Cellsmentioning
confidence: 99%